Recent advances in the structural and mechanistic aspects of Hsp70 molecular chaperones - Mayer, Matthias P.; Gierasch, Lila M. (The journal of biological chemistry, 2019)
Hsp70 chaperones are central hubs of the protein quality control network and collaborate with co-chaperones having a J-domain (an ∼70-residue-long helical hairpin with a flexible loop and a conserved His-Pro-Asp motif required for ATP hydrolysis by Hsp70s) and also with nucleotide exchange factors to facilitate many protein-folding processes that (re)establish protein homeostasis. The Hsp70s are highly dynamic nanomachines that modulate the conformation of their substrate polypeptides by transiently binding to short, mostly hydrophobic stretches. This interaction is regulated by an intricate allosteric mechanism. The J-domain co-chaperones target Hsp70 to their polypeptide substrates, and the nucleotide exchange factors regulate the lifetime of the Hsp70-substrate complexes. Significant advances in recent years are beginning to unravel the molecular mechanism of this chaperone machine and how they treat their substrate proteins.